1995
DOI: 10.1002/etc.5620141102
|View full text |Cite
|
Sign up to set email alerts
|

Biodegradation of no. 2 diesel fuel in the vadose zone: A soil column study

Abstract: Packed soil columns were used to simulate and investigate in situ biological remediation of soil contaminated with diesel fuel. We investigated and evaluated several operating strategies, including continuous flooding of the column soil with nutrient solution, and periodic operating cycles consisting of flooding followed by draining and aeration. The objectives were (a) to determine the extent of diesel fuel degradation in soil columns under four operating conditions (biologically inhibited control; continuous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

1998
1998
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 10 publications
0
8
0
Order By: Relevance
“…In fact, adding water can increase C availability, in turn increasing culturable counts of subsurface microbes by up to 200 times (Hickman and Novak, 1989). This fact is further supported by higher microbial biodegradation activity in the capillary fringe where the water table, rising and falling regularly, redistributes nutrients and possibly microbes (Lahvis et al, 1999; Widrig and Manning, 1995).…”
Section: Environmental Factors Affecting Vadose Zone Microbial Processesmentioning
confidence: 90%
“…In fact, adding water can increase C availability, in turn increasing culturable counts of subsurface microbes by up to 200 times (Hickman and Novak, 1989). This fact is further supported by higher microbial biodegradation activity in the capillary fringe where the water table, rising and falling regularly, redistributes nutrients and possibly microbes (Lahvis et al, 1999; Widrig and Manning, 1995).…”
Section: Environmental Factors Affecting Vadose Zone Microbial Processesmentioning
confidence: 90%
“…Rectangular tanks were used by Chevalier and Petersoen (1999), Cort et al (2001), and most recently Chang, Whyte, and Ghoshal (2011). Similarly, cylindrical columns were used by Angley et al (1992), Malina et al (1998), Widrig and Manning (1995), Woo andPark (1999), andPatros (2009). From the different shapes of reactors tried, the cylindrical column seems a better representation of the site remediation scenario due to the radial flow of air in the contaminated soil.…”
Section: Introductionmentioning
confidence: 99%
“…elegans. Other authors have found that minor elements such as calcium and magnesium can also affect contaminant degradation rates (Widrig and Manning 1995). Furthermore, competition for these nutrients by degrading and nondegrading species will influence the amount of contaminant degraded (Steffensen and Alexander 1995).…”
Section: Plant Mediated Increases In Nutrient Bioavailabilitymentioning
confidence: 99%